Development Patterns of Material Productivity Convergence or Divergence? - Talmon-Gros, Larissa; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
Increasing concerns regarding the world’s natural resources and sustainability continue to be a major issue for global development. As a result several political initiatives and strategies for green or resource-efficient growth both on national and international levels have been proposed. A core element of these initiatives is the promotion of an increase of resource or material productivity. This dissertation examines material productivity developments in the OECD and BRICS countries between 1980 and 2008. By applying the concept of convergence stemming from economic growth theory to material productivity the analysis provides insights into both aspects: material productivity developments in general as well as potentials for accelerated improvements in material productivity which consequently may allow a reduction of material use globally.The results of the convergence analysis underline the importance of policy-making with regard to technology and innovation policy enabling the production of resource-efficient products and services as well as technology transfer and diffusion.
Introduction -- Overuse, Scarcity and the Debate About Sustainable Development -- The Relationship Between Technological Progress and Material Consumption -- Convergence - Theory, Econometrics and Empirics -- Material Productivity Measurement -- Empirical Evidence on the Development of Material Consumption and Material Productivity -- Research Question -- Data and Descriptive Statistics -- Examination of Material Productivity Convergence -- Discussion -- Conclusion.
Keywords: Environmental economics; Economic growth; Sustainable development; Econometrics; Management; Industrial management; Environmental Economics; Economic Growth; Sustainable Development; Econometrics; Innovation/Technology Management